Lixiviation of copper content in pcb computer cards for the extraction of precious metals (2018)
The recovery of gold and silver from electronic waste is a friendly alternative to the environment that can complement the industrial production of them, usually obtained from natural ores and also to promote the reduction of such waste1. As a step prior to the recovery of these metals it is necessary to extract the copper contained in them and thus achieve a greater recovery. In the present study, the extraction2 of copper was analyzed from PCB computer cards. It began with a characterization of the metals of interest to then study their behavior in the dissolution process. Next, a process of leaching with inorganic acids was carried out at ambient conditions for six hours and mechanical agitation of 300 RPM. At the end, leaching was chosen with the highest percentage of copper extracted and a characterization of the waste was made showing that the copper content decreased from 27.09% to 1.48%. Likewise, the concentration of gold varied from 131.29 g / ton to 345.9 g / ton and that of silver from 310 g / ton to 864.8 g / ton. To verify the copper cleaning process, a leaching process was carried out with thiourea solutions, obtaining results of 74.79% and 64.8% for silver and gold, respectively.